THE USE OF MIND MAPPING TO IMPROVE STUDENT’S ABILITY IN WRITING DESCRIPTIVE TEXTS FOR SEVENTH GRADERS - Khusnul Harsul Lisan (E-LINK JOURNAL, 2022)
This study aimed to help seventh graders write descriptive writings more effectively by using mind mapping. Action research was used to describe this study. Two cycles of execution were used for the actions. The seventh graders from SMP Negeri 2 Gamping Sleman Yogyakarta served as the study's subjects. Both qualitative and quantitative data were used in the study. The students, the English teacher, and the collaborator were all interviewed after watching the teaching and learning process in action. The information was presented as field notes, interview transcripts, and pictures. While this was going on, the quantitative data were gathered by conducting pre- and post-tests following Cycle I and Cycle II. By using democratic validity, dialogic validity, catalytic validity, and result validity, the validity of the data was established. The results of the study demonstrated that using mind maps to show students how to write descriptive texts could enhance their writing abilities. Additionally, employing mind maps to teach students how to write descriptive texts might grab their interest and motivate them. According to the quantitative data, the students' mean pre-test score was 9.970, and their post-test scores for Cycle I and Cycle II were 11.191 and 13.191, respectively. The gain score at that time was 3.221. It showed that the students' writing of descriptive paragraphs significantly improved. Keywords: Mind mapping, descriptive texts, writing skill.